2021
DOI: 10.3389/fendo.2021.779365
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced Effectiveness and Comparable Safety in Biweekly vs. Weekly PEGylated Recombinant Human Growth Hormone for Children With Growth Hormone Deficiency: A Phase IV Non-Inferiority Threshold Targeted Trial

Abstract: ContextLong-acting recombinant human growth hormone (rhGH) has transformed growth hormone deficiency (GHD) treatment. However, the possibility and rationality for flexible time regimen are pending.ObjectiveWe studied the efficacy of biweekly versus weekly PEGylated rhGH (PEG-rhGH) therapy in GHD children.Design, Setting, and PatientsThis multicenter, phase IV trial with a non-inferiority threshold ≥20% enrolled 585 Tanner stage I GHD children.InterventionSubjects randomly received 0.20 mg/kg once-weekly or biw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…After 26 weeks of PEG-rhGH treatment, significant increases in Ht SDS and HV were observed in both dose groups, as expected. The incremental changes in Ht SDS and HV in the high-dose group at week 26 yielded similar results as were reported in a Phase IV clinical trial and another single-center, nonrandomized cohort study of Jintrolong ® at the same dose of 0.2 mg/kg/week ( Qiao et al, 2019 ; Sun et al, 2021 ), but were less than the results from the Phase III clinical trial of Jintrolong ® ( Luo et al, 2017 ). Changes in Ht SDS were negatively correlate with age, baseline IGF-1, and peak GH levels ( Sun et al, 2021 ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…After 26 weeks of PEG-rhGH treatment, significant increases in Ht SDS and HV were observed in both dose groups, as expected. The incremental changes in Ht SDS and HV in the high-dose group at week 26 yielded similar results as were reported in a Phase IV clinical trial and another single-center, nonrandomized cohort study of Jintrolong ® at the same dose of 0.2 mg/kg/week ( Qiao et al, 2019 ; Sun et al, 2021 ), but were less than the results from the Phase III clinical trial of Jintrolong ® ( Luo et al, 2017 ). Changes in Ht SDS were negatively correlate with age, baseline IGF-1, and peak GH levels ( Sun et al, 2021 ).…”
Section: Discussionsupporting
confidence: 75%
“…The incremental changes in Ht SDS and HV in the high-dose group at week 26 yielded similar results as were reported in a Phase IV clinical trial and another single-center, nonrandomized cohort study of Jintrolong ® at the same dose of 0.2 mg/kg/week ( Qiao et al, 2019 ; Sun et al, 2021 ), but were less than the results from the Phase III clinical trial of Jintrolong ® ( Luo et al, 2017 ). Changes in Ht SDS were negatively correlate with age, baseline IGF-1, and peak GH levels ( Sun et al, 2021 ). The mean peak GH level and mean value of IGF-1 SDS were lower in the Phase III clinical trial, which may explain the differences in growth responses in different clinical trials.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…No injection-site lipoatrophy was observed, but 1 patient from high-dose LAGH group had injection site nodules, when the patient changed the injection site the nodules disappeared. In the long-acting PEGylated rhGH phase III and phase IV randomized controlled trails, there is no injection-site lipoatrophy reported 24 25 , but some clinical study showed that at 13 weeks after GH treatment, injection-site lipoatrophy occurred, when the injection-site was changed and to avoid repeated injections on the same site, injection-site lipoatrophy recovered after 3–6 months. The other two events occurred in daily rhGH group, two patients had hyperinsulinemia, no type 2 diabetes mellitus occurred.…”
Section: Discussionmentioning
confidence: 99%